Piribedil and Pathological Gambling in six Parkinsonian patients - Federico E. Micheli; Juan C. Giugni; Micke E. De Arco Espinosa; Daniela S. Calvo; Gabriela B. Raina (Arquivos de Neuro-Psiquiatria)
Impulse control disorders (ICD) in Parkinson's disease (PD) have attracted increasing interest. They are characterized by the inability to control the impulse to perform an act that can be detrimental to them or to others. Although dopamine agonists (DA), as a group, have been associated with impulse control disorders (ICD), piribedil has rarely been reported to cause them. Method Case reports of six parkinsonian patients on piribedil presenting pathological gambling (PG). Results All of the patients presented ICD associated with piribedil use. Two of them received this medication as first treatment and four of them who had developed ICDs secondary to other DA that reappeared with piribedil. Conclusion Despite piribedil is commercially available in only a few countries, it should be considered in the differential diagnosis of PG in patients with PD.